A Sensorized Nuss Bar for Patient-Specific Treatment of Pectus Excavatum - Betti, Stefano (Sensors (Basel), 2014)
Pectus Excavatum is an anatomical deformation characterized by a depression of the anterior chest wall. Nuss technique (representing the current clinical golden standard) consists in the introduction of a corrective metal bar, in order to raise the sternum in its anatomic natural position. Nowadays, the bar plays purely a mechanical/corrective action and is kept implanted for about three years, supporting up to a maximum force of 250 N. Our study aims at optimizing the procedure of correction, in terms of monitoring the bar effect, minimizing the body response, and facilitating the bar removal. The sensorized Nuss bar prototype inserted in a platform for telemedicine described in this article is able to monitor in vitro pressure data variations, with more than 150 discrete measurements during the operating period. This behavior is promising for future clinical applications, in which the device could be exploited to monitor the forces at work, thus, providing a customized therapeutic protocol, which in turn may optimize the period of implant. The sensorized bar was also provided with a polymeric coating, able to influence human dermal fibroblast behavior in vitro. This highlights the possibility to minimize, in future in vivo applications, tissue fibrotic responses.